Fish culling reduces tapeworm burden in Arctic charr by increasing parasite mortality rather than by reducing density-dependent transmission - Henriksen, Eirik Haugstvedt; Frainer, André; Knudsen, Rune; Kristoffersen, Roar; Kuris, Armand M.; Lafferty, Kevin D.; Amundsen, Per-Arne (Journal of Applied Ecology, 2019)
This is the peer reviewed version of the following article: Henriksen, E.H., Frainer, A., Knudsen, R., Kristoffersen, R., Kuris, A.M., Lafferty, K.D. & Amundsen, P-A. (2019). Fish culling reduces tapeworm burden in Arctic charr by increasing parasite mortality rather than by reducing density-dependent transmission. Journal of Applied Ecology, 56 (6), 1482-1491, which has been published in final form at https://doi.org/10.1111/1365-2664.13369. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions. Two common Dibothriocephalus (formerly Diphyllobothrium ) tapeworm species were significantly reduced by experimental culling of their fish host Arctic charr ( Salvelinus alpinus ) in a subarctic lake. Between 1984 and 1991, funnel traps were used to cull ~35 metric tons of Arctic charr, reducing charr density by ~80%. As charr densities decreased, tapeworm prevalence and then intensity also declined over the following three decades, with D. dendriticus (formerly dendriticum ) responding faster than D. ditremus (formerly ditremum ). The two main hypotheses for how culling a host can decrease parasitism are reductions in parasite transmission due to reduced host density and reductions in parasite survival through increases in host mortality rates. We found little evidence that charr density was the main driver for reduced parasite transmission. Instead, decreased survivorship in charr, initially, through fishing‐induced changes in charr age structure, and later through increased predation rates by brown trout, led to increased parasite mortality. Although brown trout, which increased significantly after fish culling, are also hosts, they are often too big for the final host birds to eat, thus becoming parasite sinks. Synthesis and applications . Fish populations with heavy parasite burdens constitute a management problem. Our results show how fish culling can indirectly reduce transmitted parasites through increased parasite mortality. ...